4x+13=9x-26

Simple and best practice solution for 4x+13=9x-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+13=9x-26 equation:


Simplifying
4x + 13 = 9x + -26

Reorder the terms:
13 + 4x = 9x + -26

Reorder the terms:
13 + 4x = -26 + 9x

Solving
13 + 4x = -26 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
13 + 4x + -9x = -26 + 9x + -9x

Combine like terms: 4x + -9x = -5x
13 + -5x = -26 + 9x + -9x

Combine like terms: 9x + -9x = 0
13 + -5x = -26 + 0
13 + -5x = -26

Add '-13' to each side of the equation.
13 + -13 + -5x = -26 + -13

Combine like terms: 13 + -13 = 0
0 + -5x = -26 + -13
-5x = -26 + -13

Combine like terms: -26 + -13 = -39
-5x = -39

Divide each side by '-5'.
x = 7.8

Simplifying
x = 7.8

See similar equations:

| 3r^2=-3r+90 | | 23+n+6=3?4 | | 7m+12=4 | | 4n(5n^2-8n-4)= | | -3+6x=-4x-23 | | (4/3)x+(1/2)=(-5/2) | | 4(-3x+1)=-2(7x-5) | | 4y-2+y+23=7y+30-5y | | 23+n+6=34 | | 8/y+7=5/y | | (5/8)x-(3/2)=12 | | 9=-5v+7 | | 7.6x-2.3x=-95.4 | | 7+8x=2-5x | | (3/4)x-(1/2)=(1/4) | | -5+4n-7=8 | | 3(3x-4)+5x= | | (2/5)x-(1/5)=(3/5) | | -1/3x+2=4 | | 5/6d=3/15 | | 16x^2+8x-64=0 | | 8-12v-9v= | | 5x+12=7x+20 | | 2k-5/-5 | | 6x-(3x+8)=4x-43 | | 0.70x+0.05(4-x)=0.10(106) | | 5x^2+7x+20=7x^2+3-10 | | -327/180 | | 4x-44y=32 | | 4(4x^2+7x-1)= | | (4x+3)2=68 | | 4x+3(x-5)=2x+3 |

Equations solver categories